THE EFFECT OF CEO COMPENSATION, INDEPENDEN DIRECTOR AND AUDIT QUALITY ON TAX AGGRESSIVENESS - Kurnia Kurnia; Dudi Pratomo; Tommy Handoko (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
Tax is one of the largest sources of revenue from the State Budget (APBN). Every year it is expected that the achievement will be in accordance with the targets set by the government. On the other hand for Taxpayers, tax is a burden that must be reduced because it affects the profits earned. Tax avoidance by taxpayers was called tax aggressiveness, where taxpayers try to minimize the tax burden in order to increase profits.This study aims to determine the effect simultaneously and partially between tax aggressiveness as the dependent variable with executive compensation, independent director and audit quality as an independent variable with leverage control variables that were proxied by a debt to asset ratio (DAR).The research method used quantitative research with descriptive objectives verification and had a type of causality. The analytical unit used a mining company that was consistently listed on the IDX, consistently publishes financial statements and did not experience losses during the study period of 2011-2017. Based on these criteria 8 samples of the company were obtained with a study period of 7 years, resulting in 56 research samples. The method of data analysis used descriptive statistical analysis and panel data regression analysis which was assisted by Microsoft Excel 2016 and E-Views 10 Student Version software.From the results of descriptive statistical analysis and panel data regression it was concluded that executive compensation, independent directors and audit quality had an effect on simultaneously on tax aggressiveness. Partially, executive compensation and independent directors had no effect on tax aggressiveness, while audit quality had a significant negative effect on tax aggressiveness. This shows that taxpayers must pay attention to the independent variable of audit quality because it could affect tax aggressiveness